Measurement of electrons from heavy-flavour hadron decays in p-Pb collisions at $\\sqrt{s_{NN}} = 5.02$ TeV using TPC and EMCal detectors with ALICE at LHC - Jahnke, Cristiane (2016)
Heavy-ion collisions are a powerful tool to study hot and dense QCD matter, the so-called Quark Gluon Plasma (QGP). Since heavy quarks (charm and beauty) are dominantly produced in the early stages of the collision, they experience the complete evolution of the system. Measurements of electrons from heavy-flavour hadron decay is one possible way to study the interaction of these particles with the QGP. With ALICE at LHC, electrons can be identified with high efficiency and purity. A strong suppression of heavy-flavour decay electrons has been observed at high $p_{m T}$ in Pb-Pb collisions at 2.76 TeV. Measurements in p-Pb collisions are crucial to understand cold nuclear matter effects on heavy-flavour production in heavy-ion collisions. The spectrum of electrons from the decays of hadrons containing charm and beauty was measured in p-Pb collisions at $\\sqrt = 5.02$ TeV. The heavy flavour decay electrons were measured by using the Time Projection Chamber (TPC) and the Electromagnetic Calorimeter (EMCal) detectors from ALICE in the transverse-momentum range $2 < p_ < 20$ GeV/c. The measurements were done in two different data set: minimum bias collisions and data using the EMCal trigger. The non-heavy flavour electron background was removed using an invariant mass method. The results are compatible with one ($R_ \\approx$ 1) and the cold nuclear matter effects in p-Pb collisions are small for the electrons from heavy-flavour hadron decays.